Case history: integrated geophysical survey at Katarínka Monastery (Slovakia). Issue 6 (1st March 2015) - Wilken, D.; Wunderlich, T.; Stümpel, H.; Rabbel, W.; Pašteka, R.; Erkul, E.; Papčo, J.; Putiška, R.; Krajňák, M.; Kušnirák, D.
Abstract : Katarínka (St. Catherine) is the ruin of an abandoned Franciscan monastery from the early 17th century located in the western Small Carpathians in Slovakia. Historical sources and paintings suggest that, beside the remains of the monastery that are still visible, a circle of eight chapels, a pilgrim's hospice, a cemetery, and garden terraces originally surrounded the main building of the monastery. From 2009 to 2012, geophysical campaigns were performed to find evidences and positions of remains of these buildings of the monastery campus. An initial magnetic overview survey revealed multiple local accumulations of disordered dipole anomalies. Since these accumulations did not allow a structural interpretation, ground penetrating radar measurements were conducted. The ground penetrating radar results clearly showed wall structures beneath almost all magnetic anomaly accumulations. In between the remains of the monastery main building, ground penetrating radar and electrical resistivity tomography were performed at different areas that were difficult to access because of a strong cover of vegetation and steep topography.